AB0976 Association of Vitamin D Receptor Polymorphisms with Juvenile Idiopathic Arthritis (JIA). (9th June 2015) - Falcini, F.; Marini, F.; Stagi, S.; Lepri, G.; Rigante, D.; Matucci-Cerinic, M.; Brandi, M.L.
Abstract : Background: JIA is the most common chronic arthritis of childhood. Vitamin D is a potential immuno-modulator in many conditions, including autoimmune diseases. Its influence in JIA is still unclear. Specific polymorphisms of vitamin D receptor gene ( VDR ) have recently been associated with different biologic responses to vitamin D itself. Objectives: 90 Italian children, adolescents and young adults with poli- or oligoarticular onset of JIA were studied. VDR polymorphisms were analysed by PCR-based sequencing ( CDX2 in the promoter region) and PCR-based enzymatic digestions ( FokI in exon 2, BsmI and ApaI in intron 8, and TaqI in exon 9) in the genomic DNA from blood of patients. 2221 healthy Italian unrelated individuals have been used as controls for VDR polymorphism frequencies. Distribution of VDR polymorphisms has been evaluated in patients vs controls, in patients with active and inactive disease, and in patients with poli- or oligoarticular JIA. Methods: The distribution of FokI, BsmI, and TaqI polymorphisms did not show any significant difference between subjects with JIA and controls. Conversely, significant statistical differences in the distribution of CDX2 and ApaI genotypes were found, respectively with the CDX2 GG genotype (Yates-corrected chi-square 6.56; Odds ratio=1.80; p =0.0104) and the TT ApaI genotype (Yates-corrected chi-square 20.97; Odds ratio=2.67; p =0.0000), both more frequent in JIA than in controls. Also the G allele of CDX2 (Yates-corrected chi-square 6.12; Odds ratio=1.60; p =0.0134) and the T allele of ApaI (Yates-corrected chi-square 19.69; Odds ratio=2.05; p =0.0000) was more frequent in JIA. No statistical differences were found for all the analysed VDR polymorphisms, between the poliarticular vs oligoarticular forms. No significant association was found between VDR polymorphisms and active or inactive forms of JIA, neither with osteopenic or normal bone mineral density status. Conclusions: Pathogenetic mechanisms influencing the predisposition to JIA are poorly elucidated and autoimmune dysfunctions are strongly suspected. This genetic study found a significantly higher frequency of the GG genotype of VDR CDX2 polymorphism and TT genotype of VDR ApaI polymorphism in patients with JIA. The CDX2 polymorphism is located in the promoter region of the VDR gene and has been associated with VDR mRNA expression, while the ApaI polymorphism has been associated with the stability of VDR mRNA. Therefore, we can speculate that CDX2 GG genotype and ApaI TT genotype can both influence the expression of the VDR protein, presumably resulting in a reduced receptor activity with subsequent decreased response to vitamin D and potential immunity deregulation, favouring the development of JIA. Conversely, VDR polymorphisms seem not to have any influence for patients' active or non-active status, both for the oligoarticular and poliarticular form of the disease. Disclosure of Interest: None declared